A Montero auction mechanism for regulating unobserved use of the commons - Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
Regulating externalities from the use of common resources is often hampered by the regulator's inability to accurately observe individual firms' resource use. Allocating resource use through taxes on aggregate use, which often can be observed, has been suggested (Segerson, 1988); however, these taxes are vulnerable to collusion and strategic behavior and they generate inefficient entry-exit incentives. To address these disadvantages, I suggest using a Montero (2008)-type auction mechanism to allocate licenses for unobserved use of common resources and to induce compliance with these licenses through an enforcement tax on the differences between aggregated licenses issued and observed aggregated resource use.
Keywords: Q25; D62; D82; L51; 330; incentive mechanisms; unobservable resource use; non-point emissions; truthful revelation